Typification of the Linnaean names Plantago afra, P. altissima, and P. lagopus (Plantago subg. Psyllium, Plantaginaceae) - Iamonico, Duilio; Fortini, Paola; Di Pietro, Romeo (Phytotaxa, 2019)
The Linnaean names Plantago afra, P. altissima, and P. lagopus are discussed and typified with specimens preserved at LINN.